Biomaterial Stiffness of Wharton’s Jelly-Derived Mesenchymal Stem Cell-Conditioned Medium Modulates Fibroblasts Proliferation and Migration: A Preliminary Study - Choi, Sangmin; Kim, Jaeyun; Kim, Soyul; Lee, Yoonsung; Kim, Man S; Lew, Bark-Lynn; Kwon, Soon-Hyo (Annals of dermatology, 2024)
KCI Citation Count: 0